If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(c-2)=5c+6
We move all terms to the left:
4(c-2)-(5c+6)=0
We multiply parentheses
4c-(5c+6)-8=0
We get rid of parentheses
4c-5c-6-8=0
We add all the numbers together, and all the variables
-1c-14=0
We move all terms containing c to the left, all other terms to the right
-c=14
c=14/-1
c=-14
| 3x-21=6x | | 3x(2x)=294 | | 4r+122+8r+158=90 | | 3x(2x)=194 | | 4r+122=90 | | 6x+10x+12=20x+7 | | 16h=224 | | 8x7=x8 | | 44=x+54 | | -7.01+2w=10.77 | | 6.04-3b=(-2.96) | | n/4+11=15 | | 8=4-(q-2)+4 | | 2x^2+8x+36=0 | | 8r+158=180 | | 4k-3=12.08 | | 4r+122=180 | | 45=97+x | | x+3(x+2)=2(2x+2)+2 | | 3+2k=9+4k | | 15.36=9.36-3t | | 4r+122+8r+158=180 | | 1.80+0.6s=12.00 | | -5+7w=13+w | | 6x-7=6x | | 7z+9=15+5z | | d/2-4=(-2) | | 4r+122=8r+158 | | 0.1(x-10)=0.2(x-20) | | n=500 | | 4(x+15)=6x-3 | | `5x=4x-3` |